Adaptive Optimal Multiple Object Tracking Based on Global Cameras for a Decentralized Autonomous Transport System - Zhang, Xu; Scholz, Michael; Paryanto, Paryanto; Franke, Jörg (Applied Mechanics and Materials (Volume 840), 2016)

A Dynamic Simulation Model of Industrial Robots for Energy Examination Purpose - Paryanto, Paryanto; Hetzner, Alexander; Brossog, Matthias; Franke, Jörg (Energy Effiency in Strategy of Sustainable Production, 2015)
Keywords: Energy consumption; industrial robot; control system; mechatronic simulation

A Model-Based Approach for the Energy Monitoring of Handling Machines - Paryanto, Paryanto; Brossog, Matthias; Roppelt, Manuel; Franke, Jörg (Energy Efficiency in Strategy of Sustainable Production Vol. II, 2017)
Keywords: Handling systems; Energy consumption; Model-based approach; Cartesian robots; Mechatronic simulation

An integrated simulation approach to the development of assembly system components - Paryanto, Paryanto; Merhof, Jochen; Brossog, Matthias; Fischer, Christian (WGP Congress 2013 - Progress in Production Engineering, 2013)
Commonly, a modelling and simulation approach is used for parameter optimization and system behavior analysis of assembly system components. However, such simulation approaches are often not well integrated or its analysis is still based on a specific physical domain. This paper proposes an integrated simulation approach that can be used for designing, analyzing and optimizing the entire physical domain as well as the control system of mechatronic components in an assembly system. The state-of-the-art, requirements, our concept and the limitations of an integrated simulation approach are explained in this paper. A case study of the development of conveyor systems using the multi-domain simulation tool OpenModelica is also presented. On-going research shows that the integrated approach offers various benefits such as reduced development time and minimized errors, as well as maintenance during the commissioning process.
Keywords: Mechatronics; Modelling; Simulation

Chances of the Application of Multi-Domain Simulation Tools in the Field of Train System Engineering - Meinel, David; Paryanto, Paryanto; Franke, Jörg (Proceedings of the 24th FAIM Conference, 2014)
Complex mechatronic systems, such as modern trains, demand interdisciplinary software tools in order to test systems as a whole and predict operational behavior. Caused by the intention of cost savings and pushing the market launch time, computer-aided modelling and simulating of the behavior of single devices, such as thermal effects, stresses, deformations and also electrical state variables, have long since become state-of-the-art. This method leads to well-matured products. The component integration into the system as a whole, however, often causes trouble due to the lack of computer and software assistance. Furthermore, the diverse engineering fields do not have the expertise to collaborate. Therefore, joined system testing and improving is difficult and uncommon. Since the different mechanical and electrical components are being developed and tested independently, overall system behavior can hardly be forecast. As a consequence, during the system assembly phase, unpredicted incompatibilities and system malfunctions can appear. In order to integrate the train subsystems into an overall system and allow for a better synchronization and proper system testing, the application of multi-domain model-ling and simulating is recommended. In this regard, the benefits brought by multi-domain applications will be discussed in this publication, using the example of a modern train. Thereafter, a case study of a pneumatic train brake application follows. Its results are exemplary being shown to demonstrate future perspectives. Models and simulation results of the brake and air supply components already turn out allowing for comparisons with the actual system. System start-up times of the simulation match actually measured times adequately.
Keywords: Multi-Body-Simulation; Modelica

Elastohydrodynamic behavior analysis on water-lubricated journal bearing: a study of acoustic and tribological performance based on CFD-FSI approach - Tauviqirrahman, Mohammad; Jamari, J.; Bagir, Muhammad; Caesarendra, Wahyu; Paryanto, Paryanto (Journal of the Brazilian Society of Mechanical Sciences and Engineering, 2022)
Most of the studies with respect to the use of water-lubricated journal bearing are mainly concerned with tribological performance, whereas few studies explore the noise characteristics of such bearing. In this study, the tribological and acoustic behavior of water-lubricated journal bearing is studied using a rigorous program containing combined CFD and two-way FSI procedures for simulating elastohydrodynamic simulation for a range of different bearing materials. To model cavitation in the bearing, the multiphase flow mixture model is employed, while acoustical properties are investigated through broadband noise source models. The numerical results demonstrate that the bearing deformation has a great effect on the tribological characteristics of water-lubricated journal bearing, and this effect cannot be ignored, especially in the case of bearing material with a low elasticity modulus. The results also indicate that the bearing noise is weakly sensitive to the bearing material employed. Furthermore, the effect of operating conditions such as rotational speed and eccentricity ratio on the acoustic and tribological indices are also discussed in detail.
CRIS-Team Scopus Importer:2021-12-17
Keywords: Acoustic; Computational fluid dynamics (CFD); Deformation; Fluid–structure-interaction (FSI); Journal bearing; Lubrication

Energy consumption and dynamic behavior analysis of a six-axis industrial robot in an assembly system - Paryanto, Paryanto; Brossog, Matthias; Kohl, Johannes; Merhof, Jochen; Spreng, Simon; Franke, Jörg (Procedia CIRP 23, 2014)
This paper presents an experimental study to validate a dynamic model of a six-axis industrial robot as part of an assembly system and to analyze its power consumption as well as its dynamic behavior. Furthermore, the effect of robot operating parameters (i.e., payload and speed) on the power consumption and the dynamic behavior are analyzed. The investigation shows that the comparative study between simulation and experimental results can be used to improve the model's accuracy and prove that the simulation model represents the real system. Both simulation and experimental results show that the robot operating parameters strongly influence the industrial robot's power consumption and dynamic behavio
Keywords: Energy simulation; Industrial Robot; Systems Engineering

Energy Consumption Modeling of a Turning Table and Standardized Integration into Virtual Commissioning - Hauf, Dominik; Kruck, Julian; Paryanto, Paryanto; Franke, Jörg (Procedia Manufacturing, 2017)
This paper describes the standardized integration of energy models into the virtual commissioning tool chain for a holistic energy consumption and peak power simulation of production cells used in the automotive industry. An energy model of a turning table as part of a demonstration cell is built in detail using modeling language Modelica. Further, an interface description for model connection to virtual commissioning is presented. Finally, simulation results are validated by measurements on a real demonstrator.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Energy efficency; functional mock-up interface (FMI); physics based modeling; sustainable manufacturing; virtual comissioning

Energy consumption modeling within the virtual commissioning tool chain - Hauf, D.; Meike, D.; Paryanto, Paryanto; Franke, Jörg (IEEE International Conference on Automation Science and Engineering, 2015)
In this paper an energy modeling approach within the virtual commissioning tool chain is presented. Virtual commissioning (VCom) today is a de facto methodology for programmable logic controller (PLC) software design and validation for automatic production systems. Energy consumption has never been an optimization criterion in VCom. Concepts of energy consumption modeling for any production unit have been investigated for measuring, visualization and optimization of control strategies. The hardware-in-the-loop simulation includes logical behavior models, the respective energy models and 3D-kinematic models of the production units, which are connected over common industrial bus network with a hardware-PLC. The concept has been developed for use with commercially available software tools so that the research results are implementation-oriented. An example from the automotive industry has been used.
CRIS-Team Scopus Importer:2023-03-07

Energy Planning of Manufacturing Systems with Methods-Energy Measurement (MEM) and Multi-Domain Simulation Approach - Bornschlegl, Martin; Paryanto, Paryanto; Spahr, Michael; Kreitlein, Sven; Bregulla, Markus; Franke, Jörg (Applied Mechanics and Materials, 2014)
Energy costs play a decisive role in the operation costs of automotive production companies. Therefore, energy planning in an early conception and planning stage becomes an important topic. This is because the early conception and planning stage has the greatest potential to influence the energy consumption of manufacturing technologies since about 70-80 % of the energy costs are committed during this stage. However, lifetime cost and specifically energy consumption are currently not a determining factor at this stage. The reason is that the prediction of energy costs for complex manufacturing systems are challenging. Previous research approaches in the area of energy planning are limited to detailed planned production. A standardized approach to determine the energy consumption rates at an early stage does not exist. In this context, the EffiPLAS project has therefore proposed to solve this challenge. The aim of this project is to develop a Methods-Energy Measurement approach with elementary energy elements to support the planning process at an early stage, and to develop a modular simulation model for calculating the energy consumption of industrial robots, which complements the energy prediction. In this paper, the basic concept of elementary energy units and their value determination techniques are presented, and the simulation model is outlined. The developed approach will help to predict the prospective energy consumption of complex production equipment so that energy costs can be accounted for in an improved manner within a life-cycle cost comparative analyses.
Keywords: Energy consumption; Energy efficiency; Energy simulation; Industrial robots; Methods-energy measurement (MEM); Production planning

Hydrodynamic lubrication analysis of hydrophobic textured journal bearing considering cavitation - Tauviqirrahman, Mohammad; Jamari; Muchammad; Ardiansyah, Azis; Setyana, Budi; Paryanto, Paryanto (Cogent Engineering, 2022)
Lubricated contact performance can be improved by using a textured surface as well as a hydrophobic surface. A procedure to obtain the optimal partially textured journal bearing combined with the hydrophobic coating is presented through the computational fluid dynamics (CFD) codes. In this study, lubricated hydrophobic textured contacts with and without cavitation modeling are discussed. The cavitation phenomena in the lubricant is modeled using a multiphase model of "mixture" to obtain a realistic condition. The effect of dimple depth, as well as the eccentricity ratio, on the tribological performance, is of particular interest. It is found that the tribological performance is greatly influenced by the multiphase flow cavitation scheme. When cavitation modeling is taken into account, higher load support is noted. Furthermore, the simulation results show that a hydrophobic textured surface with a shallow depth (d/h (min)<1) seems to be better for enhancing the tribological performance. Meanwhile, for the case of the low eccentricity ratio, there is an optimal dimple depth giving the highest load support. The findings explored in this work can be considered as a theoretical basis to increase the performance of hydrophobic textured journal bearing.
CRIS-Team WoS Importer:2022-06-10

Investigation of the Tribological Performance of Heterogeneous Slip/No-Slip Journal Bearing Considering Thermo-Hydrodynamic Effects - Tauviqirrahman, Mohammad; Afif, M. Fadhli; Paryanto, Paryanto; Jamari, J.; Caesarendra, Wahyu (Fluids, 2021)
The slip boundary has an important influence on hydrodynamic journal bearing. However, less attention has been paid to the positive effect of slip on thermal behaviour. In this study, a computational fluid dynamics (CFD) analysis investigating the thermo-hydrodynamic (THD) characteristics of heterogeneous slip/no-slip bearings running under steady, incompressible, and turbulent conditions is presented. A comprehensive analysis is made to investigate the THD behaviours of heterogeneous slip/no-slip bearings in terms of lubricant pressure, temperature distribution, volume fraction of vapor, and load-carrying capacity when they are running under different shaft rotational speeds. The multiphase cavitation model is adopted to represent the real operational condition of the journal bearing. Numerical results show that the load-carrying capacity of the heterogeneous slip/no-slip bearing can be significantly increased by up to 100% depending on the rotational speed. It is also observed that there is an optimal journal rotational speed for maximizing the load-carrying capacity. An insightful new finding is revealed in a numerical framework, wherein it is found that by introducing the heterogeneous slip/no-slip pattern, the maximum temperature can be reduced by up to 25% in comparison with a conventional bearing.
CRIS-Team WoS Importer:2021-03-19

Mechatronic Behavior Analysis of a Customized Manufacturing Cell - Paryanto, Paryanto; Brossog, Matthias; Merhof, Jochen; Franke, Jörg (Proceedings of the 7th World Conference on Mass Customization, Personalization, and Co-Creation (MCPC 2014), Aalborg, Denmark, February 4th - 7th, 2014, 2014)
Analyzing the mechatronic behavior of a manufacturing cell used in a customized manufacturing process is a difficult task with numerous obstacles. Therefore, a method that can be easily used for developing and optimizing a customized manufacturing cell, i.e., universal contacting module (UCM) cell, for the in-circuit testing of electronic modules is desired. In this paper, we present a convenient method using multi-domain simulation tools for analyzing the mechatronic behavior of the UCM cell. The UCM cell, which consists of mechatronic components such as a six-axis industrial robot and conveyor systems, were successfully modeled, simulated, and validated under several payloads. This work also presents a modeling procedure that can be applied by system engineers with a basic background in control systems for analyzing the mechatronic behavior of manufacturing cell components.
Keywords: Multi-Domain Simulation; mechatronic behavior; manufacturing

Methodology Towards Computer-aided Testing of Complex Mechatronic Systems: A Case Study about Assembling a Train System - Meinel, David; Paryanto, Paryanto; Franke, Jörg (Procedia CIRP, 2016)
Domain-specific computer-aided analysis of technical systems has become well-established. Nominal and worst case scenario behavior of systems can be modelled sufficiently, however, still lacking the ability of simulating the behavior of technical systems as a whole, combining single-domain subsystems. Therefore, unpredictable failure can occur, which displays the demand for computer-aided system analysis. To counteract the foresaid, a concept has been proposed, which enables sufficient designing and implementing a highly flexible model landscape. It serves the process from comprehending a technical system's specifications and functions towards an executable model structure, using the Modelica-based modelling software SimulationX. Since its future application remains to be tested in the aftermath, the concept will exemplarily be applied on a flexible train simulator.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Computer-aided testing; Flexible simulator; Mehatronic system modelling; SimulationX; Train modelica; Train simulator; Train systems

Reducing energy consumption of industrial robots in manufacturing systems - Paryanto, Paryanto; Brossog, Matthias; Bornschlegl, Martin; Franke, Jörg (International Journal of Advanced Manufacturing Technology, 2015)
Reducing the energy consumption of industrial robots (IR) that are used in manufacturing systems has become a main focus in the development of green production systems. This is due to the reality that almost all automated manufacturing processes are using IR as the main component. Thus, reducing the energy consumption of IR will automatically reduce operating costs and CO2 emissions. Therefore, a method for reducing the energy consumption of IR in manufacturing systems is desired. Firstly, this paper presents a literature survey of the research in energy consumption analysis of IR that is used in manufacturing processes. The survey found that current research in this field is focused on the development of simulation models of IR that are able to be used to predict its energy consumption. Secondly, a modular model to analyze power consumption and dynamic behavior of IR is developed. Afterward, an experimental investigation is carried out to validate and estimate the accuracy of the model developed. The investigation shows that the developed modular model can be conveniently used to optimize the industrial robot’s operating parameters, which are commonly needed for production planning and at the process optimization stage. In addition, the investigation shows that the process constraints, environment layout, productivity requirement, as well as the robot payload and operating speed are the key factors that must be considered for optimizing the productivity and efficiency of IR.
Keywords: Energy efficiency; Industrial robots; Power consumption; Manufacturing systems; Production planning; Operating parameters